Providing teaching resources for young learner classes: Best practices in efl context - Isry Laila Syathroh; Bachrudin Musthafa; Pupung Purnawarman (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2019)
The availability of teaching resources is one of important factors to create successful lessons in teaching English to young learners (TEYL). Teachers can use flashcards, toys, songs, rhymes, books, audio visual materials, digital recourses and others to support teaching and learning process. Ready-made materials are available in stores, however they are usually expensive. The aim of this article is to share one of the best practices in providing resources for young learners in learning English. In the academic year of 2018, 40 students of English Department of IKIP Siliwangi took English for Young Learners (EYL) course for two credit hours. This is the second subject which is related to teaching young learners after they learned TEYL subjects as the perquisite subject in the previous year. In this course, students re-learned the concept of TEYL and the concepts how to provide teaching materials and resources for TEYL classes. At the end of the course, they should show their projects and demonstrate how to use them in TEYL. The findings reveal that students’ are very creative in designing resources for TEYL classes. This ability is very crucial in order to create child-friendly pedagogy in EYL classrooms.